The Forgotten Spongy Myocardium: Clinical Trajectory of Left Ventricular Noncompaction Cardiomyopathy in an Asymptomatic Adult - Leonardo Paskah Suciadi; Dony Yugo Hermanto; Surya Sinaga Immanuel; Jason Wirandy Haryanto; Harvian Satya Dharma (The Indonesian Heart Association, 2026)
Background: Left Ventricular Noncompaction (LVNC) is a rare cardiomyopathy characterized by a thin compacted epicardial layer and an extensive noncompacted endocardial layer with prominent trabeculations and deep intertrabecular recesses that communicate with the Left Ventricular (LV) cavity. The classic triad of complications includes chronic heart failure, ventricular arrhythmias, and systemic embolic events. At present, evidence-based management guidelines remain limited. Case Illustration: We report a 42-year-old man with LVNC, initially detected as an incidental Left Bundle Branch Block (LBBB) on Electrocardiogram (ECG) during a routine medical checkup. Although he remained asymptomatic, LV Ejection Fraction (LVEF) progressively declined, accompanied by rising N-Terminal pro-B-type Natriuretic Peptide (NT-proBNP) levels. Coronary artery disease was excluded by coronary computed tomography angiography. Given worsening LV systolic function over 2 years, Cardiac Magnetic Resonance (CMR) demonstrated an LVNC phenotype consistent with cardiomyopathy. Guideline-Directed Medical Therapy (GDMT) for heart failure was initiated, along with oral anticoagulation for primary prevention of LV thrombus. After medication optimization, LVEF improved markedly, and NT-proBNP normalized. Conclusions: This case illustrates the value of comprehensive evaluation and multimodality imaging in patients with unexplained LBBB, even when asymptomatic. Early diagnosis, phenotype-guided treatment, and longitudinal surveillance may help prevent clinical progression and future heart-failure, arrhythmic, or thromboembolic complications.